2021
DOI: 10.3390/s21103388
|View full text |Cite
|
Sign up to set email alerts
|

Pedestrian Detection in Blind Area and Motion Classification Based on Rush-Out Risk Using Micro-Doppler Radar

Abstract: Various remote sensing technologies have been applied in intelligent vehicles and robots for surrounding-environment recognition. However, these technologies experience difficulties in detecting pedestrians in blind areas and their motions, such as rush-out behaviors. To address this issue, we present a radar-based technique for the detection of pedestrians in blind areas and the classification of different risks of rush-out behaviors among detected pedestrians. We verify their ability to detect pedestrian mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
(23 reference statements)
0
0
0
Order By: Relevance
“…They showed that it is possible to detect moving road users outside the direct line-of-sight with reflected radar measurements by using building facades or parked vehicles as relay walls. In [34], the authors explicitly addressed the detection of fully occluded, darting out pedestrians with radar. They designed an experimental setup with a static radar sensor in an indoor area (behind a corner) and an outdoor area (behind a van).…”
Section: B Radar Based Approachesmentioning
confidence: 99%
“…They showed that it is possible to detect moving road users outside the direct line-of-sight with reflected radar measurements by using building facades or parked vehicles as relay walls. In [34], the authors explicitly addressed the detection of fully occluded, darting out pedestrians with radar. They designed an experimental setup with a static radar sensor in an indoor area (behind a corner) and an outdoor area (behind a van).…”
Section: B Radar Based Approachesmentioning
confidence: 99%
“…Many approaches have been suggested to minimize the line of sight-related traffic hazards. One approach is based on ensuring intelligent collaboration between infrastructure and vehicles, such as vehicle-to-vehicle and vehicle-to-infrastructure communication [4]. However, this approach is more realistic in urban areas as it is economically hard to extend to most non-urban and rural roadways.…”
Section: Introductionmentioning
confidence: 99%
“…However, this approach is more realistic in urban areas as it is economically hard to extend to most non-urban and rural roadways. A second approach is based on the propagation characteristics of radio waves at blind areas such as in [4]. However, these techniques assumed that radio waves reach blind areas through multiple reflections by walls on a side of the road.…”
Section: Introductionmentioning
confidence: 99%